ASSOCIATION OF DELETION 13Q14 WITH CLINICOPATHOLOGIC FEATURES IN CHRONIC LYMPHOCYTIC LEUKEMIA - Ali Ahmed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of Del 13q14 in Chronic lymphocytic leukaemia, to compare its association with clinicpathologic features and to define the contribution of this abnormality to the prognosis.